Prevalence and Identification of Species of Eimeria Causing Coccidiosis in Poultry Within Vom, Plateau State, Nigeria - Saidu, L.; Wakawa, A.M.; Abdu, P.A.; Adene, D.F.; Kazeem, H.M.; Ladan, K.C.; Abdu, M.; Miko, R.B.; Fatihu, M.Y.; Adamu, J.; Mamman, P.H. (International Journal of Poultry Science, 2008)
A survey for the prevalence of coccidiosis and identification of species found in Vom, Plateau state, Nigeria, was undertaken. A total of 300 samples made up of one hundred carcasses and two hundred faecal droppings from nine different poultry farms were investigated during the months of April to June. The prevalence of coccidial infection among adult bird was 36.7% and among the younger birds was 52.9%. The species of Eimeria identified included E. tenella, E. maxima, E. necatrix and E. acervulina.